Identidade como Territorialidade em trabalhos de Arte Contemporânea - Genioli, Ana Amélia Corazza (2005)
Through the reading of theoretical texts and contemporary works of art this research examines three aspects of the concept of frontiers or borders: frontiers between individuals and territory between individuals and communities and frontiers inside the art system itself The methodology used did not focus on one specific area of knowledge instead it covered several areas under the auspices of the theory of communication (Sodré 2002 Greiner e Katz 2005 e Sebeok 1991) artistic research (Miwon Kwon 2002) and some topics discussed under the aegis of cognitive science (Lakoff e Johnson 1987) as well as the theory of culture (Bhabha 1998 Shohat e Stam 1998) The first chapter investigates the concept of space transformed into place through the mediation of the individual and how in artwork determinate elements can designate categories The works themselves inform through signs which are the product of the artist s expression in a certain ambient that will be understood by the spectator or participant through the mechanisms that organize communicational systems It also analyses situations where the media itself is transformed into ambience The two following chapters concern situations outside the individual focus and also contextualize situations of frontiers from the point of view of individuals in communities It presents strategies of resistance to discourses given a priori based on narratives of in-between places and the comprehension of plural and partial identities The third chapter also analyses artwork and theory concerning the relativisation of systems and the fouth chapter concerns the work of three artists that consider the limits set by the art system itself The focus of this work has been developed from the tensions conflicts and ambiguities referring to the notion of frontier established by cultural constructs From the undestanding of the process of construction of these senses emerges the necessity for new options that will propose alternative concepts including concepts concerning curatorial work as disscussed at the end of this dissertation The questioning of cultural frontiers affects the curatorial experience as it highlights the relational nature of a group of work their signifying components and their context as open sense a continuum that gravitates between political posture and artist creation